Formative self-and peer assessment for improved student learning: the crucial factors of design, teacher participation and feedback. Issue 7 (3rd October 2018) - Wanner, Thomas; Palmer, Edward
Abstract: Self and peer-assessment are becoming central aspects of student-centred assessment processes in higher education. Despite increasing evidence that both forms of assessment are helpful for developing key capabilities in students, such as taking more responsibility for their own learning, developing a better understanding of the subject matter, assessment criteria and their own values and judgements, and developing critical reflection skills, both forms of assessment are still not the norm at universities. This paper provides the findings of a two-year study of formative self and peer-assessment at an Australian university. The study supports other research showing that students tend to regard formative self and peer-assessment as beneficial for gaining more insights about the assessment process and for improving their own work. We argue that self and peer-assessment requires careful design and implementation for it to be an effective tool for formative assessment processes; and that the development of students' capacities for giving feedback, and the continuous and timely involvement of the teacher, are central aspects for successful self and peer-assessment. The move to self and peer-assessment is not simple for teachers and students but is worthwhile and necessary for twenty-first century higher education.